Evaluación del cumplimiento de políticas públicas aplicadas sobre la educación en la Dirección Distrital De Educación 13D07 Chone-Flavio Alfaro período 2020-2022 - Molina Segovia, Erika Lisbeth (2024)
The objective of this Curricular Integration Work was to evaluate the compliance with public educational policies in the District Directorate of Education 13D07 Chone-Flavio Alfaro period 2020-2022 for continuous improvement for the benefit of the population. It adheres to a mixed methodological approach, due to the use of quantitative and qualitative research methods and techniques. In addition, descriptive and inferential statistics were used for data processing, analysis and representation. Among the results, it was identified that the district faces challenges that affect the fulfillment of public educational policies, such as: inadequate management and mastery of public technological resources by the educational community. The lack of commitment and empowerment of the educational community in the different activities implemented by the Ministry of Education and developed in educational institutions. The impact of public policies was determined, which is at a medium level, according to the respondents, it is due to the issue of infrastructure, which affects the practice of learning. Therefore, it is concluded that it is necessary to implement strategies that allow the eradication of the critical knots identified, and it is recommended to implement the proposal of the plan that contributes to strengthening the participation of students in educational establishments, fortifying the adaptation of school coexistence, promoting activities where empathy and an active attitude are promoted, Improve the quality of student learning with an equity approach, increase and strengthen the quality of school management.